2008
DOI: 10.1063/1.2976355
|View full text |Cite
|
Sign up to set email alerts
|

Slipping friction of an optically and magnetically manipulated microsphere rolling at a glass-water interface

Abstract: The motion of submerged magnetic microspheres rolling at a glass-water interface has been studied using magnetic rotation and optical tweezers combined with bright-field microscopy particle tracking techniques. Individual microspheres of varying surface roughness were magnetically rotated both in and out of an optical trap to induce rolling, 2 along either plain glass cover slides or glass cover slides functionalized with polyethylene glycol. It has been observed that the manipulated microspheres exhibited non… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Since the speed of motion is largest near f c , the total distance that a microsphere moves during a fixed time interval (here ∆t = 10 s) will also be largest near f c , and therefore, this zigzag pattern of motion will be most easily observed just above f c . Agayan et al [15] observed similar effects in rotating fields for both free microspheres on a glass surface, as well as for microspheres that were trapped by optical tweezers at the surface, and found shifts in the direction of motion relative to the plane of the rotating field of up to 10 • for field rotation frequency above a critical value f c ≈ 2.5 Hz. This was interpreted as a tilt of the direction of the magnetic moment away from the plane of rotation into the third dimension.…”
Section: Motion Of Remanent Magnetic Beads In Asynchronous Rotationmentioning
confidence: 71%
See 2 more Smart Citations
“…Since the speed of motion is largest near f c , the total distance that a microsphere moves during a fixed time interval (here ∆t = 10 s) will also be largest near f c , and therefore, this zigzag pattern of motion will be most easily observed just above f c . Agayan et al [15] observed similar effects in rotating fields for both free microspheres on a glass surface, as well as for microspheres that were trapped by optical tweezers at the surface, and found shifts in the direction of motion relative to the plane of the rotating field of up to 10 • for field rotation frequency above a critical value f c ≈ 2.5 Hz. This was interpreted as a tilt of the direction of the magnetic moment away from the plane of rotation into the third dimension.…”
Section: Motion Of Remanent Magnetic Beads In Asynchronous Rotationmentioning
confidence: 71%
“…Optical tweezers have been used to trap magnetic microspheres near a surface [15], and the particles were then exposed to rotating magnetic fields. Due to the rotation of the particles, the equilibrium trapping position of the particles was displaced relative to the center of the optical trap.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Ding et al on rolling friction of microspheres [20] demonstrate that even on the micro-scale spheres can roll with little slip. A study by Agayan et al of the slipping friction of optically and magnetically manipulated microspheres on a glass-water interface demonstrate techniques for manipulation that may benefit from our methodology [21].…”
Section: B Sphere Manipulationmentioning
confidence: 97%
“…This is also seen in S obtained in the STO regime for the AT and related CG rollers, with even larger " s . The overall increase of S with " s is caused by the decreased slipping and increased traction of the roller [29].…”
mentioning
confidence: 98%